FACTORS INFLUENCING EMPLOYEE JOB PERFORMANCE IN PRIVATE BANK EMPLOYEES IN WEST JAKARTA - Turangan, Joyce A.; Ruslim, Herman (Graduate Program of Universitas Tarumanagara, 2025)
Several companies regard employees as crucial assets due to their role in the company's success. Therefore, it's imperative for companies to retain employees to prevent turnover. Employees perform optimally and are more productive when supported by a positive, conducive work environment. Companies must strive to recruit talented employees who meet qualifications and offer attractive compensation and benefits to motivate them, ensuring they feel valued and recognized. This study aims to examine the positive influence of perceived self-efficacy on knowledge sharing, the positive impact of perceived self-efficacy on perceived environmental support, the positive effect of perceived environmental support on knowledge sharing, and to analyze the role of perceived environmental support as a mediating variable between knowledge sharing and employee job performance in private banks in West Jakarta. The study utilizes a quantitative approach, employing non-probability sampling and convenience sampling methods. Data collection involves distributing online questionnaires to 81 employees in private banks in West Jakarta, with data analysis conducted using SmartPLS3. Results revealed that perceived self-efficacy positively affects knowledge sharing. However, perceived self-efficacy did not significantly impact employee job performance. Knowledge sharing was found to have a positive influence on employee job performance, but this relationship was not statistically significant. Perceived environmental support was found to positively influence both knowledge sharing and employee job performance, consistent with existing literature. However, knowledge sharing did not mediate the relationships between perceived self-efficacy or perceived environmental support and employee job performance, indicating the presence of complex factors influencing these dynamics.